Good governance practices and its relation to public trust at Ipoh City Council Perak / Abdul Rauf Muthokhir, Aishah Umira Shamsudin and Marni Ghazali - Muthokhir, Abdul Rauf; Shamsudin, Aishah Umira; Ghazali, Marni (2021)
Malaysia is one of the countries that successfully developed its plans (Hafiz, Aziz & Said, 2015). According to Khotami (2017), a clear government in the country is important as a part of good governance practices. As highlighted by Khalid, Alam, and Said (2016) and Obiero (2018), good governance practices are very important to increase public trust. Most importantly, a study conducted by Mohamed, Aly Kalam, Othman, Omar, and Rahman (2017) mentioned that the integrity of illness remains critical and the level of trust among the public remains the same. Omar et al. (2017) stated that despite many initiatives taken by the government, but the integrity deficiency issue is still shackling the civil services and not showing any signs of reduction. According to Hafiz, Azizal, Farahwahida, and Jamaliah (2015), the major challenges for a government are to strengthen ethics and integrity to enhance positive feedback from the public which is the receiver. The issue of integrity is a significant problem in the Malaysian public sector. Since integrity is also one of the important pillars of good governance practices.